Pengaruh Game Online Terhadap Perilaku Prokrastinasi Siswa Kelas 5 Sekolah Dasar Negeri Cemoro - almuntaqo zainuddin; Novialdi Firmansyah Cahya Baskara (Elementary Teacher Education Program, Majalengka University, 2023)
This study tried to identify the influence of online games on the procrastination behavior of grade 5 elementary school children of SD Negeri Cemoro. The research method utilizes quantitative methods, the sampling technique used in the study is total sampling, for a sample of 51 respondents. The data obtained is then processed using the SPSS 24 program, with descriptive quantitative analysis techniques to obtain or provide an explanation of the actual situation and respond to questions about the state of the research topic. The results of this study indicate a significant influence between playing online games and procrastination behavior of grade 5 children in Cemoro State Elementary School, it was concluded that online games contribute to procrastination behavior towards grade 5 children in Cemoro State Elementary School along with the findings of the chi-square test found a p-value of < 0.05. Students who rarely play online games who very often behave proktasination does not exist, students who rarely play online games who often behave proktasination as much as 22% and students who do not behave proktasination as much as 78%. Students who played online games who had no procitation behavior as much as 2%, students who played games who sometimes behaved proxtasination often as much as 62% and students who played games who very often behaved proxtasination as much as 36%.